Appropriateness of colonoscopy at a tertiary care centre – are we overdoing gastrointestinal endoscopy? - Nerma Čustović; Lejla Džananović; Ismar Rašić; Nadža Zubčević; Lejla Šaranović-Čečo; Jasmina Redžepagić (Medicinski glasnik, 2020)
Aim: To evaluate the pattern of indications and a spectrum of colonic pathology, and to determine appropriateness of indications for colonoscopy in order to improve patient selection for colonoscopy. Methods: This retrospective study includes 294 patients who were referred to the Gastroenterology Department from a primary care physician in order to approach endoscopic examination. Study data included patients’ anamnestic data (comorbidities, positive family history, performed radiological examinations) an indication for the procedure, and colonoscopy findings. Results: Haematochezia was confirmed in 186 (63.26%), positive radiologic finding in183 (62.24%) and anaemia in 157 (53.40%) patients. Adenoma and colorectal carcinoma were detected in 40 (13.6%) and 53 (18%) patients, respectively. A significant association between haematochezia and colorectal neoplasm was confirmed (p=0.019), haematochezia and inflammatory bowel disease (p=0.027), and between radiological finding and colorectal neoplasm (p=0.018). There was no significant association between anaemia and any of the colonoscopic findings. According to EPAGE II criteria indications were appropriate in 187 (63.6%), uncertain in 67 (22.8%) and inappropriate in 40 (13.6%) patients. Conclusion: This study confirmed a slightly larger number of uncertain and inappropriate indications for colonoscopy compared to other studies that examined indications for colonoscopy, which can be attributed to a high number of patients with functional bowel disorders.
Keywords: colonic diseases/diagnosis; colorectal neoplasm; polyps; utilization